RECURRENT SELECTION FOR GENERAL AND SPECIFIC COMBINING ABILITY IN MAIZE - Zeyad A. Abdulhamed,; Nihad.M. Abood,; Abdulsamad. H. Noaman, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to identify efficiency  of recurrent  selection program to improve maize population. This program was applied to var. Buhooth 106 with var. 5012  Using RGCA  with the inbred Zm7 for the production of RSCA. The recurrent selection program was implemented for four consecutive seasons (2020 - 2021) at the Fields Station of the College of Agriculture - University of Anbar. In the spring season 2020, 100 top crosses  were obtained from both varieties and progeny.  During the fall season 2020, an experiment was carried out to compare the top crosses of each variety RGCA and RSCA using a 10 × 10 partially balanced lattice design.. Six genotypes from each genetic population as well as Buhooth 106 and 5012 and Zm7 inbreds). The genotype-S1-2 RSCA achieved the lowest female flowering period for females 61.50 days, the highest number of rows per ear 17.80 rows, and the highest grain yield 177.82 g. The genotype-S1-3 RSCA achieved the highest leaf area 0.593 m2 and the highest number of kernels per row 43.11 kernel. The broad sense heritability of the traits of the number of rows and the number of kernels in the row and the yield of the plant reached 53.23%, 73.85% and 41.94%, respectively, and high genetic advance for kernels per row and grain yield of 4.79 and 15.52 respectively.